The Mediating Role of e-WOM in the Relationship between e-Service Quality, e-Trust, and Repurchase Intention: A Study of Traveloka Users in Indonesia - Yulia Kusumawardani; Putu Indah Rahmawati; Ni Luh Wayan Sayang Telagawathi (International Journal of Management Science and Information Technology, 2026)
The rapid growth of the online travel industry in Indonesia has intensified competition among Online Travel Agent platforms, highlighting the importance of understanding factors influencing repurchase intention. This study aims to examine the effects of e-service quality and e-trust on repurchase intention, with e-WOM as a mediating variable, among users of Traveloka. A quantitative causal research design was employed, involving 190 respondents selected through purposive sampling. Data were collected using a structured Likert-scale questionnaire and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The findings reveal that e-service quality has a positive and significant effect on both repurchase intention and e-WOM. E-trust significantly influences repurchase intention but does not significantly affect e-WOM. Furthermore, e-WOM positively affects repurchase intention and partially mediates the relationship between e-service quality and repurchase intention. However, e-WOM does not mediate the relationship between e-trust and repurchase intention. These results indicate that e-service quality serves as the primary driver of repurchase intention, both directly and indirectly through positive electronic word-of-mouth, while e-trust functions mainly as a direct determinant of repeat purchase decisions.